PROGRAM THREE ENDS UNTUK MENGAKHIRI KESENJANGAN EKONOMI BAGI PEREMPUAN DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH (STUDI PADA DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK PROVINSI SUMATERA SELATAN) - Liani, Evi; Antasari, Rina; Lusiana, Lusiana (Program Studi Muamalah Fakultas Syariah dan Hukum, 2020)
This research is entitled Three Ends Program to End Economic Gap for Women in the Perspective of Sharia Economic Law (Study at the Office of Women's Empowerment and Child Protection, South Sumatra Province). The background of this research is that women are often considered to have many limitations in their participation in economic activities. Women's obligations are considered only in social activities in the family. This shows a gap between men and women in economic activity. In fact, women have an important role in economic activities, especially to increase family income, if the woman is responsible for the economy for her family. Based on this background, the writer wants to know more about: First, how is the implementation of the three ends program to end economic inequality for women in the Office of Women's Empowerment and Child Protection, South Sumatra Province? Second, how do the three ends program to end economic inequality for women from the perspective of Islamic economic law? The method used in this research is field research with data collection techniques, namely observation, interviews, and documentation at the Office of Women's Empowerment and Child Protection of South Sumatra Province and with data analysis techniques in the form of data reduction, data presentation and drawing conclusions. The results of this study can be concluded that the implementation of the three ends program to end economic inequality for women in the Office of Women's Empowerment and Child Protection of South Sumatra Province, namely by helping women to have businesses in home industry activities and PRIMA Village in the form of goods or business equipment assistance and business training. This program does not conflict with the principles of sharia economic law and is very suitable for the benefit of improving the family economy.